2018
DOI: 10.1186/s40792-018-0555-8
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous ureteral rupture caused by iliac aneurysm: a case report

Abstract: BackgroundRupture of the ureter with extravasation resulting from an iliac aneurysm is extremely rare. Herein, we report a case of ureteric rupture with urinary extravasation secondary to an iliac aneurysm.Case presentationAn 80-year-old man was admitted to our hospital for sudden onset of severe abdominal pain. Contrast-enhanced computed tomography demonstrated a large left internal iliac aneurysm (6.5 cm in diameter) and a ureteric rupture with leakage of contrast media from the left ureter, indicating a spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Serra RM, et al [15] reported that ureteral obstruction does not occur from the bulging of the aneurysm itself, but rather from the perianeurysmal inflammatory and fibrotic processes. However, with a rapid expansion of an aneurysm with impending rupture, the bulge might induce ureteral extravasation before the compensatory mechanisms of the ureter can function [14]. Our patient had a small left renal artery aneurysm without associated inflammatory characteristics and with-out fibrosis, so it cannot correlate the SUR with the presence of aneurysm.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Serra RM, et al [15] reported that ureteral obstruction does not occur from the bulging of the aneurysm itself, but rather from the perianeurysmal inflammatory and fibrotic processes. However, with a rapid expansion of an aneurysm with impending rupture, the bulge might induce ureteral extravasation before the compensatory mechanisms of the ureter can function [14]. Our patient had a small left renal artery aneurysm without associated inflammatory characteristics and with-out fibrosis, so it cannot correlate the SUR with the presence of aneurysm.…”
Section: Discussionmentioning
confidence: 82%
“…Sato H, et al [14] in 2018 reported a case of SUR caused by iliac aneurysm. The majority of ureteral obstruction cases involve inflammatory aneurysms or retroperitoneal fibrosis associated with perianeurysmal fibrosis that ultimately results in the structural compromise of the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…The injury is usually identified during the procedure and is repaired prior to significant urinoma development. Following this, less than 4% of penetrating traumatic insults and of 1% blunt traumatic insults resulted in ureteral injuries [1][2][3][4][5][6]. Because of the infrequency in traumatic presentation and the general origin being surgical intervention, it is a rare presentation in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…A review of PubMed studies suggests that there are three general origins for a urinoma: an obstructive process in addition to the already mentioned traumatic incidents or iatrogenic origins. Obstructive processes can include ureterolithiasis, retroperitoneal fibrosis, or intra-abdominal mass effect [3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Additional remarkable treatment modalities and techniques which may be found in case reports or small case series are: retrograde trans-gluteal approach for embolization [24][25][26] parallel stent-graft technique for IIIAA exclusion 27,28 deployment of an iliac branch device to exclude the hypogastric aneurysm [29][30][31][32] endovascular exclusion exploiting the distal branches of the hypogastric artery as landing zones 33 Excluded noteworthy papers regarding clinical presentation-besides what we described in our qualitative synthesis-included: ureterohydronephrosis, ureteral rupture or haematuria [34][35][36][37] sciatic pain 38 arteriovenous fistula 39,40 deep venous thrombosis and pulmonary embolism 41 ileus, or bowel obstruction 42,43 aortoenteric fistula 44,45…”
Section: Excluded Noteworthy Case Reportsmentioning
confidence: 99%